ANALISIS HUKUM TENTANG CALON PRESIDEN DAN CALON WAKIL PRESIDEN REPUBLIK INDONESIA - Mustajab, Muhammad; Burlian, Paisol (Program Studi Muamalah Fakultas Syariah dan Hukum, 2019)
The 2019 President and Vice President General Election of the Republic of Indonesia is a democratic process to elect the President and Vice President of the Republic of Indonesia 2019-2024. This general election process not only aims to determine the change of head of state, but also as a concept of the functioning of a democratic system. This is because in a democratic election system is part of the constitutional rights of every citizen that has been guaranteed by our constitution. Sovereignty is in the hands of the people and implemented according to the Basic Law. That is the main principle of the source of state power, namely the sovereign people and the Basic Law guarantees the exercise of sovereignty.